2008
DOI: 10.4028/www.scientific.net/amr.41-42.233
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Effect on Vibration Signatures of Cracks in Railway Prestressed Concrete Sleepers

Abstract: Abstract. In general, cracks in structural members indicate a level of serviceability of the engineering structures. Usually a hairline crack can be detected by visual inspection, crack gauge, fibre optical sensor, or laser sensor. Recently, an attempt to develop a non-destructive tool for health monitoring of prestressed concrete sleepers in railway tracks using the vibration responses has been established at the University of Wollongong, Australia. However, the fundamental understanding of the dynamic effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…The results showed that the rail pad parameters have the nonlinear effects on the effective stiffness significantly influencing the first three modes of the in situ track system, and can remarkably affect the frequencies and mode shapes of the further modes. Kaewunruen and his colleague have also theoretically investigated the dynamic effect on vibration signatures of cracks in concrete sleepers (Kaewunruen and Remennikov 2008a). They concluded that cracks in concrete sleepers weaken their flexural stiffness, resulting in the decrease in resonance frequencies.…”
Section: Review Of the Literaturementioning
confidence: 97%
See 1 more Smart Citation
“…The results showed that the rail pad parameters have the nonlinear effects on the effective stiffness significantly influencing the first three modes of the in situ track system, and can remarkably affect the frequencies and mode shapes of the further modes. Kaewunruen and his colleague have also theoretically investigated the dynamic effect on vibration signatures of cracks in concrete sleepers (Kaewunruen and Remennikov 2008a). They concluded that cracks in concrete sleepers weaken their flexural stiffness, resulting in the decrease in resonance frequencies.…”
Section: Review Of the Literaturementioning
confidence: 97%
“…They concluded that cracks in concrete sleepers weaken their flexural stiffness, resulting in the decrease in resonance frequencies. They also showed that the damping coefficient tends to increase with crack incurrence (Kaewunruen and Remennikov 2008a). Besides works made at UW, several attempts have been made worldwide but less directly related to the experimental evaluation of dynamics of concrete sleepers.…”
Section: Review Of the Literaturementioning
confidence: 98%
“…The causes of the dynamic augments vary from irregularities in the geometry of the track structure, the surface of the rail or the wheel; to the vehicle operating speed; and the mass of the vehicle suspension characteristics (Esveld, 2001). Impact loads are infrequent but have high magnitude and short duration, and their typical magnitudes in the reviewed cases of freight traffic vary roughly between 100 kN and up to 750 kN, depending on the causes and the travelling speed of the train (Reminnikov & Kaewunruen, 2008). In case of high-speed lines, loading is even higher.…”
Section: Introductionmentioning
confidence: 97%
“…The substructure includes ballast, sub-ballast, subgrade and formation, while the superstructure includes sleepers, rail pads, fasteners and rails (Kaewunruen & Reminnikov, 2008). Sleepers are the track components of the ballasted track which rest on the ballast formation transversely, provide support and fixation to the rails and transmit the stresses to the lower layers.…”
Section: Introductionmentioning
confidence: 99%
“…The typical full-scale prestressed concrete sleepers as shown in Figure 2, which are often used in broad gauge tracks, were selected for these tests. The dimensions and shape of the prestressed concrete sleepers used in the impact tests can be found in the companion paper [6]. The average compressive strength of cored concrete is 88.5MPa in accordance with AS1012.14 [7].…”
Section: Experimental Overviewmentioning
confidence: 99%